Proposed Digital Marketing Strategy To Increase Patient Visits In Premier Bintaro Hospital - Hanif Yuditama, Rafi; Furinto, Asnan (GEMA EKONOMI, 2023)
The COVID-19 pandemic has had an extraordinary impact on all business sectors, including the healthcare industry. This has undoubtedly created a negative stigma towards hospitals and has led to frightening experiences when visiting them. COVID-19 has also changed hospital marketing strategies from offline methods to online methods. Premier Bintaro Hospital is a private hospital located in South Tangerang, which offers excellent services such as an Orthopedic center, spine center, vascular center, stroke center, and arthroplasty. According to internal data from Premier Bintaro Hospital, the number of patient visits has decreased during the COVID-19 pandemic, and the number of visits has not yet returned to pre- pandemic levels. To address this issue, this research was conducted using both qualitative and quantitative methods. The qualitative method involved observation and interviews during the process of business immersion. The quantitative method involved a questionnaire with 162 respondents. This research analyzed business issues using internal and external factors. Internal factors were analyzed using STP analysis, marketing mix 7P analysis, and VRIO analysis. External factors were analyzed using PESTLE analysis, competitor analysis, and customer analysis. The combination of these factors resulted in a SWOT analysis for Premier Bintaro Hospital. The proposed business solution to the problem is to implement strategies using a new STP strategy, an integrated marketing communication strategy, and a social media strategy. All strategies are aligned with the objectives desired by Premier Bintaro Hospital to increase their number of patient visits post-COVID-19 pandemic.